2019
DOI: 10.3389/fnut.2019.00050
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Metabolic Properties of Bovine Milk Oligosaccharides and Their Potential in the Development of Novel Therapeutics

Abstract: Among the many bioactive components in human milk, the free oligosaccharides (OS) have been intensely studied in recent decades due to their unique ability to selectively modulate the infant gut microbiota, in addition to providing numerous other health benefits. In light of the demonstrated value of these compounds, recent studies have set out to characterize the structures and properties of the similar and more widely-available OS in the dairy industry. This mini review gives a brief overview of the common a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 72 publications
(107 reference statements)
2
27
0
1
Order By: Relevance
“…However, cross-feeding was only sparsely observed, with light production of butyrate and propionate, as expected for preweaning infants [69]. Given the fact that a low pH has been correlated with the inhibition of pathogenic bacteria [70][71][72], and SCFA to be beneficial for the intestinal health [73][74][75][76], this study confirmed BMOS as potent prebiotic, in alignment with other studies [31]. Despite the consistent prebiotic effects of BMOS, interindividual variability was observed among the 10 donors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, cross-feeding was only sparsely observed, with light production of butyrate and propionate, as expected for preweaning infants [69]. Given the fact that a low pH has been correlated with the inhibition of pathogenic bacteria [70][71][72], and SCFA to be beneficial for the intestinal health [73][74][75][76], this study confirmed BMOS as potent prebiotic, in alignment with other studies [31]. Despite the consistent prebiotic effects of BMOS, interindividual variability was observed among the 10 donors.…”
Section: Discussionsupporting
confidence: 85%
“…Sazawal and colleagues [ 27 ] reported a reduction in bloody diarrhea, days with fever, and the prevalence of ear infection in infants consuming B. lactis (HN019) together with GOS. More recently, Bovine Milk-derived OligoSaccharides (BMOS) were proposed as a valid alternative to GOS [ 28 , 29 , 30 , 31 ]. BMOS, as described by Meli and colleagues [ 32 ], are derived from demineralized whey permeate.…”
Section: Introductionmentioning
confidence: 99%
“…The milk fat globule membrane (MFGM) in raw bovine milk contains components (lipids, proteins, and carbohydrates) that are believed to interact with the gut microbiome of the growing infant (Bourlieu et al, 2017). In addition, bovine milk contains various kinds of oligosaccharides that can also promote the establishment of a healthy gut microbiome (Oliveira, Wilbey, Grandison, & Roseiro, 2015;Robinson, 2019). As a result, these milk constituents may provide protection against inflammatory diseases and contribute to the development of a healthy immune system.…”
Section: Gastrointestinal Fatementioning
confidence: 99%
“…Presently, due to having the highest concentration among human milk oligosaccharides, 2 -FL is the best characterized and tested oligosaccharide which is added to infant's formula [15]. By 2019, nearly 200 US patents on adding 2 -FL as a food ingredient had been reported [157]. Recently, two detailed reviews concerning the addition of individual HMOs, namely fucosylated 2 -FL and non-fucosylated lacto-N-neotetraose (LNnT), to different infant formulas by Reverri and coworkers [158] and by Vandenplas and coworkers [15], respectively, were published.…”
Section: Fucosylated Hmos and Bovine Glycoproteins In Infant Formulamentioning
confidence: 99%
“…Moreover, recent reports [16,157] show that interest in the addition of fucosylated oligosaccharides, mainly 2 -FL, is growing not only for infant formula, but also in highly specialized food preparations that can be used in the clinic and which are extremely important for the health of the general public. Additionally, to meet the needs, new techniques have been developed that allow the determination of fucosylated milk oligosaccharides such as 2 -FL and 3-FL not only in breast milk, but also to control levels in commercially available infant formulas [164].…”
Section: Fucosylated Hmos and Bovine Glycoproteins In Infant Formulamentioning
confidence: 99%